Study of Phonological Awareness in Children with Phonological Disorders - Leila Ghasisin; Sara Mirani; Mehdi Tazhibi (University of Social Welfare and Rehabilitation Sciences, 2013)
Objective: The relationship between phonological awareness and phonological disorders has been considered in recent decades. Phonological awareness deficits in children with phonological disorders could be due to a deficit in phonological abilities. The present study attempts to study the phonological awareness deficits in children with phonological disorders.  Materials & Methods: This was a comparative and cross-sectional study. The research sample consisted of 25 children with phonological disorders and 25 normal children. Children with phonological disorders were selected by convenience sampling method and normal children were selected by matching with the disordered group. The research instruments consisted of the "phonetic information test" to determine the phonological disorders and the "phonological awareness test" to assess phonological awareness. The awareness of syllable blending and syllabification, rhyme and alliteration was also studied. The data were analyzed using SPSS-13, based on paired t-test, independent T-test and Chi-square. Results: The mean score of phonological awareness in children with phonological disorders was significantly lower than normal children (P<0.001). There was no significant difference between the two groups in terms of awareness of syllabification (P=0.073) and syllable blending (P=0.189). But there was a significant difference between the two groups in terms of awareness of rhyme (P<0.001) and alliteration (P<0.001) Conclusion: The findings showed that children with phonological disorders are at a lower level than normal children in terms of phonological awareness. According to the results of this study, it can be recommended that the speech-language pathologists should consider phonological awareness when treating children with phonological disorders.